Fast fabrication of NiO@graphene composites for supercapacitor electrodes: Combination of reduction and deposition - Hui, Xu (Mater Des, 2016)
Graphene-based inorganic composites have been attracting more and more attention since the attachment of inorganic nanoparticles instead of conducting polymeric materials to graphene sheets turns out higher capacitances and good capacity retention. Here we report a fast fabrication method to prepare NiO@graphene composite modified electrodes for supercapacitors. By this method, preparation of electrochemical active materials of NiO/graphene and modification of the electrode can be simultaneously performed, which is achieved separately by traditional method. Moreover, the problem of poor adhesion of active materials on the surface of the electrode can be well solved. The NiO particles introduced to the films exhibit pseudocapacitive behavior arising from the reversible Faradaic transitions of Ni(II)/Ni(III) and greatly improve the capacitance of the electrodes. With the increase in NiO content, highly reduced graphene can be obtained during cyclic voltammetry sweeping, leading to the increase in the electrode capacitance. The highest specific capacitance of the constructed electrodes can reach 1258 F/g at a current density of 5 A/g.